Marketing Medicines for Self-Medication, Is it a Good or Bad Idea - Dr. Rehan Haider (International Journal on Economics, Finance and Sustainable Development, 2022)
Over-the-counter (OTC) medicines, also known as nonprescription medicines, refer to medications that can be purchased without a prescription and are safe and effective when used according to the directions on the label, and as directed by a healthcare professional (Food and Drug Admini, 2018).1 Self-medication is becoming increasingly popular around the world. According to studies, the global prevalence of self-medication ranges from 11.2 to 93.7%, depending on the target population and country (Balbuena et al., 2009;2 Kasulkar and Gupta, 2015; 3 Arrais et al., 2016; 4 Håkonsen et al., 2016;5 Prado et al., 2016; 6 Gama and Secoli, 2017; 7 Helal and Abou-ElWafa, 2017; 8 Abdi et al., 2018;9 Kassie et al., 2018; 10 Lei et al., 2018; 11 Tesfamariam et al., 2019). 12 This means a large proportion of the world’s population uses drugs without first consulting a doctor or healthcare professional. Countries differ with regards to where nonprescription medicines to be sol d. In many countries, they are restricted to pharmacies, even though in some of these countries a pharmacist is not always present. In others, some medicines are restricted to pharmacies while others may be sold outside of pharmacy. In still others, such as the United States, all non-prescription medicine sold in any outlet. The reasoning is that if it is safe enough to be used in self-medication, the labeling is adequate to assure safe and effective use in culture where the pharmacist has a long tradition of a monopoly on medicines, such as in majority of the countries of the European Union (EU), all medicines are restricted to sale in a pharmacy.